2020
DOI: 10.3390/ijerph17155527
|View full text |Cite
|
Sign up to set email alerts
|

Smokers’ and Nonsmokers’ Receptivity to Smoke-Free Policies and Pro- and Anti-Policy Messaging in Armenia and Georgia

Abstract: Garnering support for smoke-free policies is critical for their successful adoption, particularly in countries with high smoking prevalence, such as Armenia and Georgia. In 2018, we surveyed 1456 residents (ages 18–64) of 28 cities in Armenia (n = 705) and Georgia (n = 751). We examined support for cigarette and electronic nicotine delivery systems (ENDS)/heated tobacco product (HTP) smoke-free policies in various locations and persuasiveness of pro- and anti-policy messaging. Participants were an average age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 26 publications
3
20
0
Order By: Relevance
“…Figure 3 shows the 41 countries and areas from WPR ( n = 4) [56–60, 62–65, 68, 70, 71, 73, 74], EUR ( n = 35) [32–38, 40, 42–45] and AMR ( n = 2) [34, 47, 49–51, 53–55], for which prevalence of current HTP use in the general population was reported with ages 9 years and older included in the analyses. The pooled current use prevalence estimate across all available countries and areas was 1.53% (95% CI = 1.22, 1.87) ( I 2 = 99%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 3 shows the 41 countries and areas from WPR ( n = 4) [56–60, 62–65, 68, 70, 71, 73, 74], EUR ( n = 35) [32–38, 40, 42–45] and AMR ( n = 2) [34, 47, 49–51, 53–55], for which prevalence of current HTP use in the general population was reported with ages 9 years and older included in the analyses. The pooled current use prevalence estimate across all available countries and areas was 1.53% (95% CI = 1.22, 1.87) ( I 2 = 99%).…”
Section: Resultsmentioning
confidence: 99%
“…Five additional studies that met inclusion criteria were identified from e-mail alerts and the grey literature search. A total of 45 included studies reported on 38 national surveys, covering four regions from 42 countries and areas: 15 studies from EUR [32][33][34][35][36][37][38][39][40][41][42][43][44][45] (Armenia, Austria, Belgium, Bulgaria, Croatia, Cyprus, Czechia, Denmark, Estonia, Finland, France, Georgia, Germany, the United Kingdom, Greece, Hungry, Ireland, Italy, Kosovo, Latvia, Lithuania, Luxembourg, Malta, Montenegro, the Netherlands, North Macedonia, Poland, Portugal, Romania, Serbia, Slovakia, Slovenia, Spain, Sweden and Ukraine), 11 studies from AMR [34,[46][47][48][49][50][51][52][53][54][55] (Canada and the US), 19 studies from the WPR [56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74] (Hong Kong, Japan, South Korea and Taiwan) and one study from AFR…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study used a matched-pairs community-randomized controlled trial to examine the effectiveness of local coalitions in promoting smoke-free air among 28 communities in Armenia and Georgia (matched and randomized by key characteristics, e.g., population). The ongoing parent study is more fully described elsewhere [27,28].…”
Section: Ongoing Study Overviewmentioning
confidence: 99%
“…Among all 28 intervention and control communities, population-level surveys (i.e., of community members) were conducted before the launch of the coalition member training (October-November 2018) [28] and will then be conducted at the culmination of coalition activity. Current analyses focused on baseline population-level surveys conducted in October-November 2018.…”
Section: Data Collectionmentioning
confidence: 99%